Przemówienie Rektora KUL Ks. Prof. dra hab. Stanisława Wilka na otwarcie sympozjum „Jan Paweł II a antyk chrześcijański” - Wilk, Stanisław (Vox Patrum, 2007)
Speech of the Rector of KUL, Rev. Prof. Stanisław Wilk at the Opening of the Symposium "John Paul II and Christian Antiquity"